Prepositions and Particles in English : a Discourse-functional Account. - O'Dowd, Elizabeth M. (Oxford University Press, 1998)
A discourse-functional account of the categories preposition and particle in English. Explaining why certain words have membership in both categories and solving puzzles associated with the syntax and semantics of these words. The author provides new insights into how prepositions and particles are used and how their meaning can change.